2009
DOI: 10.1111/j.1365-2222.2009.03249.x
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin is involved in migration of eosinophils in asthma

Abstract: These results indicate that OPN plays a role in the migration of eosinophils into the airways and may be involved in the pathogenesis of asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
2
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(65 citation statements)
references
References 34 publications
5
57
2
1
Order By: Relevance
“…At present, the role of OPN seems to be complex, because contradictory reports have been published regarding the contribution of OPN in several inflammatory conditions [8,14,15] and dual roles of this molecule in a single disease have also been reported [16,17,34,35]. Xanthou et al recently showed that after Ag sensitization and pulmonary challenge, the levels of Ag-specific IgE were higher in OPN À/À mice when compared with OPN 1/1 mice, while administration of anti-OPN Ab during Ag sensitization suppressed Ag-specific IgE production [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the role of OPN seems to be complex, because contradictory reports have been published regarding the contribution of OPN in several inflammatory conditions [8,14,15] and dual roles of this molecule in a single disease have also been reported [16,17,34,35]. Xanthou et al recently showed that after Ag sensitization and pulmonary challenge, the levels of Ag-specific IgE were higher in OPN À/À mice when compared with OPN 1/1 mice, while administration of anti-OPN Ab during Ag sensitization suppressed Ag-specific IgE production [16].…”
Section: Discussionmentioning
confidence: 99%
“…OPN's potential involvement in Th2-associated allergic responses has been investigated recently, particularly in eosinophilic airway inflammation [16,17] and in mast cell degranulation [18]. However, its role in systemic allergen sensitization via the production of allergen-specific IgE is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] Further, several human studies have suggested that osteopontin level is increased in airway of asthmatic subjects and is associated with various asthma phenotypes. 15,[20][21][22] Additionally, the chromosomal region of 4q24 where SPP1 gene is located (4q21-q25) has been reported to be associated with atopy and with atopic disease in asthmatic subjects. 28,29 Together, these studies suggest that the osteopontin gene, SPP1, is a reasonable candidate gene for asthma susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…15 In addition, several recent studies have reported an increased level of osteopontin in bronchoalveolar lavage fluid and induced sputum in asthmatic subjects. [20][21][22] A recent genetic association study in a Japanese population has reported an association between genetic variant in the osteopontin gene, SPP1, and total serum immunoglobulin E (IgE) levels in nonasthmatic subjects, thus suggesting that osteopontin may participate in the regulation of basal IgE production. 23 Based on these observations, we hypothesized that putative functional polymorphisms in SPP1 is a risk factor for asthma and asthma phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, there are reports suggesting that this protein participates in the pathogenesis of asthma. Several studies have demonstrated that OPN level is increased in asthmatic patients and is associated with disease phenotypes [113][114][115][116]. In addition, the chromosomal region of 4q24 (where OPN gene is mapped) has been associated with atopy in asthmatic patients [117].…”
Section: Asthmamentioning
confidence: 99%